2014
DOI: 10.1038/hdy.2014.30
|View full text |Cite
|
Sign up to set email alerts
|

MHC class II diversity of koala (Phascolarctos cinereus) populations across their range

Abstract: Major histocompatibility complex class II (MHCII) genes code for proteins that bind and present antigenic peptides and trigger the adaptive immune response. We present a broad geographical study of MHCII DA b1 (DAB) and DB b1 (DBB) variants of the koala (Phascolarctos cinereus; n ¼ 191) from 12 populations across eastern Australia, with a total of 13 DAB and 7 DBB variants found. We identified greater MHCII variation and, possibly, additional gene copies in koala populations in the north (Queensland and New So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 54 publications
0
25
0
Order By: Relevance
“…Also consistent with Lau et al (2014), koalas had four to five DAB variants and one to two DBB variants identified per individual, and the DAB*19 and DAB*21 variants were found in a majority of koalas (96.8% and 98.9%, respectively), and were therefore not included in analyses. Although three new “genotype patterns” were identified from OSCP analyses, sequencing of these patterns showed that they comprised new combinations of previously identified MHCII variants.…”
Section: Resultsmentioning
confidence: 69%
“…Also consistent with Lau et al (2014), koalas had four to five DAB variants and one to two DBB variants identified per individual, and the DAB*19 and DAB*21 variants were found in a majority of koalas (96.8% and 98.9%, respectively), and were therefore not included in analyses. Although three new “genotype patterns” were identified from OSCP analyses, sequencing of these patterns showed that they comprised new combinations of previously identified MHCII variants.…”
Section: Resultsmentioning
confidence: 69%
“…Although limited MHC diversity does not necessarily condemn a species to extinction (e.g., Castro‐Prieto, Wachter, & Sommer, ; Lau, Jaratlerdsiri, Griffith, Gongora, & Higgins, ; Plasil et al., ; Weber, Stewart, Schienman, & Lehman, ; Weber et al., ; Zhu, Ruan, Ge, Wan, & Fang, ), low MHC diversity can compromise population viability over the long term by increasing susceptibility to disease (Belov, ; Radwan, Biedrzycka, & Babik, ; Segelbacher et al., ; Spielman, Brook, Briscoe, & Frankham, ). In particular, many species are likely to increasingly encounter novel pathogens in the future because of increased exposure to humans, their livestock, other domesticated animals (e.g., feral dogs and cats), and invasive species (Barrett, Brown, Junge, & Yoder, ; Daszak, Cunningham, & Hyatt, , ).…”
Section: Discussionmentioning
confidence: 99%
“…Physiographic factors such as big rivers and mountains can influence the genetic structure of different species, especially those lacking dispersal ability (Bushar et al., ; Lau, et al, ). As expected, substantial differences were found in genetic structure among the three geographic populations (Figure , Tables and ).…”
Section: Discussionmentioning
confidence: 99%